The effect of price and service quality on the decision to choose Shopee e-commerce in Kibing Village Batam - Shandrya Victor Kamanda (Institute of Computer Science (IOCS), 2023)
Marketing is the tip of the horn of a business entity or company because with marketing a company can find out the number of sales from the marketing results carried out by a marketer. This study aims to determine the effect of service on the decision to choose Shopee e-commerce in Batu Aji Batam District. The population in this paper is 585 people. And the sample obtained was 87 people taken by random sampling method. The data analysis used is multiple regression and hypothesis testing and uses SPSS version 22. The conclusion obtained is that the price variable partially has a significant effect on the decision to choose, the service quality variable partially has a significant effect on the decision to choose. The price and service quality variables together have a significant effect on the decision to choose Shopee e-commerce in Kibing Village, Batam